2018
DOI: 10.1186/s12877-018-0752-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic medications in older people in residential care facilities and associations with quality of life: a cross-sectional study

Abstract: Background: Psychotropic medications have been associated with many adverse outcomes in older people living in residential care. Home-like models of residential care may be preferable to traditional models of care and we hypothesized that this model may impact on the prevalence of psychotropic medications. The objectives were to: 1) examine associations between psychotropic medications and quality of life in older adults living in residential care facilities with a high prevalence of cognitive impairment and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 30 publications
1
20
1
1
Order By: Relevance
“…A more recent study in Australia (n= 322,120) found that 50% of the participants had a diagnosis of dementia, and the prevalence of antipsychotic dispensing was 21.3%, benzodiazepines 30.5% and antidepressants 38% [34]. Comparing to above two larger studies [33,35], the prevalence of psychotropic medicines was higher in our study (antipsychotics and benzodiazepines 39% and antidepressants 42%). This ndings in our study is not surprising as all the participants recruited in our study are those having advanced dementia.…”
Section: Discussioncontrasting
confidence: 71%
“…A more recent study in Australia (n= 322,120) found that 50% of the participants had a diagnosis of dementia, and the prevalence of antipsychotic dispensing was 21.3%, benzodiazepines 30.5% and antidepressants 38% [34]. Comparing to above two larger studies [33,35], the prevalence of psychotropic medicines was higher in our study (antipsychotics and benzodiazepines 39% and antidepressants 42%). This ndings in our study is not surprising as all the participants recruited in our study are those having advanced dementia.…”
Section: Discussioncontrasting
confidence: 71%
“…These are key indicators of medication use quality, given the well-documented risk of harm associated with these medicines, the high prevalence of dementia and potentially problematic psychotropic agent use in Australian RACF. 29,30 Reducing the number of prescribed medications was a similar outcome reported in a recent systematic review evaluating outcomes of medication reviews in RACF residents both with and without dementia. 36 Multi-faceted interventions, inclusive of collaborative pharmacist-led medication reviews in residents both with and without dementia, have demonstrated efficacy in reducing inappropriate psychotropic medication use.…”
Section: Discussionmentioning
confidence: 75%
“…28,29 Psychotropic drug use in residents with dementia is associated with reduced quality of life and increased adverse outcomes, including stroke, falls, hospital admissions and mortality. 30 Medication reviews aim to improve quality use of medicines and reduce the risk of adverse events. 31 Quality use of medicines refers to 'best-possible' medicines use where treatment benefits are maximised, and risk of associated harms is minimised.…”
mentioning
confidence: 99%
“…Low quality of life has been documented as prevalent among African Americans [ 59 , 60 , 61 , 62 ]. Harrison and colleagues (2018) found that an increased number of psychotropic medications in individuals was associated with poorer self-rated health and quality of life [ 63 ].…”
Section: Discussionmentioning
confidence: 99%